Targeting BACE1 to restore functional angiogenesis in type 2 diabetes. (10th June 2022) - Clavane, E; Cubbon, RM; Caolo, V; Meakin, PJ
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation British Microcirculation and Vascular Biology Society Background: β-site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1) is a transmembrane aspartyl protease notorious for its contribution to amyloid plaque formation in the pathophysiology of Alzheimer's disease (AD) [1]. Further research has suggested a role for BACE1 in vascular homeostasis [2, 3] and has shown that it proteolytically cleaves various angiogenic signalling factors including VEGF receptor 1 (VEGFR1) [2], NOTCH ligands [4] and the insulin receptor [5]. Similar to AD, BACE1 activity is elevated in models of type 2 diabetes [5], suggesting a potential role for its contribution to aberrant vessel growth characteristic of diabetes-related complications. Purpose: Type 2 diabetes dramatically increases an individual's risk of developing microvascular complications and consequent lower limb amputations [6]. Therefore, identifying novel roles for BACE1 in angiogenic dysregulation will aid progression of future biomedical interventions in this field. Methods: Retinal staining and the fibrin gel angiogenesis assay were used to identify a role for BACE1 in vessel growth in vivo and in vitro, respectively. Endothelium of the developing retinal vasculature in BACE1-/- and wild type (WT) mice was stained with IsolectinB4-Alexa488 and imaged using confocal microscopy. Sprout formation was further analysed using the fibrin gel angiogenesis assay with human umbilical vein endothelial cells (HUVECs) treated with or without a highly specific BACE1 inhibitor or transfected to over-express BACE1. Primary isolated pulmonary endothelial cells (PECs) were isolated from BACE1-/- and wild type control mice prior to Western blots, and real-time PCR. Results: BACE1-/- retinas had increased branch points, vasculature area and quantity of filopodia compared to WT mice. Moreover, BACE1-/- PECs had reduced NOTCH1 signalling (26.73% ± 14.15, P=0.05) and soluble Jagged-1 protein (28.48% ± 14.61, P=<0.05). HUVECs treated with a BACE1 inhibitor had increased sprouting (18.70%± 5.92, P=<0.05) as well as increased phosphorylation of eNOS (83% ± 22, P=<0.05) and Akt (85.5% ± 9.24, P=NS) compared to untreated cells. Moreover, HUVECs transfected to over-express BACE1 had decreased sprouting (35.22% ± 7.34, P=<0.01) and increased NOTCH1 signalling (23.4% ± 2.42, P=0.01). Conclusion: Our findings indicate a role of BACE1 in negatively regulating angiogenesis, possibly via NOTCH1 or Akt/eNOS/NO signalling. This provides a potential therapeutic purpose for BACE1 inhibitors, previously trialled to treat AD, in normalising BACE1 levels in individuals with type 2 diabetes and preventing associated microvascular complications.